PENGARUH FREE CASH FLOW, RETURN ON INVESTMENT DAN INFLASI TERHADAP DIVIDEND PAYOUT RATIO PADA PT. PANCA USAHA PALOPO PLYWOOD TAHUN 2013-2017 - .... ........ (Program Studi Perbankan Syariah, IAIN Palopo, 2018)
AbstractThe purpose of this study was to examine and determine the effect of free cash flow, return on investment and inflation on the dividend payout ratio at PT. Panca Usaha Palopo Plywood. The data used in this study, namely time series data in the form of financial statements of PT. Panca Usaha Palopo Plywood for 2013-2017 and inflation data obtained from the Central Bureau of Statistics. The results showed that Free Cash Flow has a positive effect on the Dividend Payout Ratio at PT. Panca Usaha Palopo Plywood, so that hypothesis 1 is accepted, Return on Investment has a positive effect on the Dividend Payout Ratio at PT. Panca Usaha Palopo Plywood, so that hypothesis 2 is accepted and inflation has a negative effect on the Dividend Payout Ratio at PT. Panca Usaha Palopo Plywood, so that hypothesis 3 is accepted.Keyword: dividend payout ratio; market based accounting research; plywood AbstrakTujuan penelitian ini adalah untuk menguji dan mengetahui pengaruh free cash flow, return on investment dan inflasi terhadap dividend payout ratio pada PT. Panca Usaha Palopo Plywood. Data yang digunakan dalam penelitian ini, yakni data time series berupa laporan keuangan PT. Panca Usaha Palopo Plywood tahun 2013-2017 serta data inflasi yang diperoleh dari Biro Pusat Statistik. Hasil penelitian menunjukkan bahwa Free Cash Flow berpengaruh positif terhadap Dividend Payout Ratio pada PT. Panca Usaha Palopo Plywood, sehingga hipotesis 1 diterima, Return on Investment berpengaruh positif terhadap Dividend Payout Ratio pada PT. Panca Usaha Palopo Plywood, sehingga hipotesis 2 diterima dan Inflasi berpengaruh negatif terhadap Dividend Payout Ratio pada PT. Panca Usaha Palopo Plywood, sehingga hipotesis 3 diterima.Keyword: dividend payout ratio; market based accounting research; plywood DAFTAR PUSTAKAAli Al-Twaijry, Adulrahman. 2007. Dividend Policy and Payout Ratio: Evidence from the Kuala Lumpur Stock Exchange. The Journal of Risk Finance, Vol. 8 Iss 4 pp. 349-363, Emerald InsightAlzomania, Turki SF dan Al-Khadhiri, Ahmed. 2013. Determination of Dividend Policy: The Evidence from Saudi Arabia. International Journal of Business and Social Science, Vol. 4 No. 1; January 2013Amidu, Mohammed dan Abor, Joshua. 2006. Determinants of Dividend Payout Ratios in Ghana. The Journal of Risk Finance, Vol. 7 Iss 2 pp. 136-145, Emerald InsightBoban, Ivan. 2011. Determinants of Dividend Payout Ratio: Evidence from The UK, The Journal of Risk Finance, Vol. 12 Iss 12 pp. 11-48, Emerald InsightChasanah, Nur Amalia, 2008. Faktor-faktor yang Mempengaruhi Dividend Payout Ratio (DPR) pada Perusahaan yang Listed di Bursa Efek Indonesia. Tesis Program Pasca Sarjana Magister Manajemen Universitas DiponegoroCrutchley, C and Hansen, R. 1989. A Test of the Agency Theory of Managerial Ownership, Corporate Leverage and Corporate Dividends. Financial Management, Vol. 18, pp. 36-76Dwiyani Rini, Hadiwidjaja. 2007. Analisis Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio pada Perusahaan Manufaktur di Indonesia. Tesis Sekolah Pascasarjana Universitas Sumatera Utara.Erkaningrum, Indri. 2007. Determinan Dividend Payout Ratio pada Perusahaan-Perusahaan Manufaktur di Indonesia. Jurnal Bisnis dan Akuntansi “Analisis”, Volume 01, No.01, November 2007 (ISSN: 1978–9750, Halaman 86Gill, et al. 2010. Determinants of Dividend Payout Ratios: Evidence from United States. The Open Business Journal, 2010, Volume 3, page 8-14Gordon, M.J. (1963). Optimum Investment and Financing Policy. Journal of Finance. 264-272Hatta, Atika Jauhari. 2002. Faktor-faktor yang Mempengaruhi Kebijakan Dividen: Investasi Pengaruh Teori Stakeholder. JAAI Volume 6 No.2, Desember 2002Hermuningsih, Sri. 2007. Analisis Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio pada Perusahaan Yang Go Public di Indonesia. Jurnal Ekonomi & Pendidikan, Volume 4 Nomor 2, November 2007Jensen, M., and Meckling W. 1976. Theory of the firm: Managerial behavior, agency cost, and ownership structure. Journal of Finance Economics. 3: 305-360Karya Utama, I Made. 2014. Dividend Payout Ratio dan Faktor yang Mempengaruhinya (Studi pada Bursa Efek Indonesia periode 2006-2010). Simposium Nasional Akuntansi, Lombok, 2014Khan, Waseem dan Ashraf, Naheed. 2014. In Pakistani Service Industry: Dividend Payout Ratio as Function of some Factors. International Journal of Academic Research in Accounting, Finance and Management Sciences, Vol. 4, No.1, January 2014, pp. 390-396Komrattanapanya, Pornumpai dan Suntrauk, Phasswan. 2013. Factors Influencing Dividend Payout in Thailand: A Tobit Regression Analysis. International Journal of Accounting and Financial Reporting, ISSN 2162-3082, 2013, Vol. 3, No. 2Kumar, Suwendra. 2007. Analisis pengaruh Struktur Kepemilikan, Investment Opportunity Set (IOS), dan Rasio-Rasio Keuangan Terhadap DPR. Tesis Program Pasca Sarjana Magister Manajemen Universitas DiponegoroMarlina, Lisa dan Danica Clara. 2009. Analisis Pengaruh Cash Position, Debt to Equity Ratio, dan Return on Assets terhadap Dividend Payout Ratio.Jurnal Manajemen Bisnis, Vol 2, No.1, 2009Miller, M.H dan Modigliani, F. 1961. Dividend policy, growth, and the valuation of shares. Journal of Business. 34: 411-433Puspita, Fira. 2009. Analisis Faktor-faktor yang Mempengaruhi Kebijakan Dividend Payout Ratio. Tesis Program Pasca Sarjana Universitas Diponegoro, SemarangSekaran, Uma. 2006. Research Methods for Business, 4th Edition. Buku 1. Terjemahan oleh Kwan Men Won. 2009. Jakarta: Salemba EmpatSudarsono, Heri. 2005. Bank dan Lembaga Keuangan Syari’ah. Edisi kedua. Yogyakarta: EKONISIA.Sugiyono. 2011. Statistik unuk Penelitian. Bandung: AlphabetaSuherli, Michell dan Sofyan Safri harahap. 2004. Studi Empiris terhadap Faktor Penentu Kebijakan Jumlah Dividen. Media Riset Akuntansi, Auditing, dan Informasi, Volume 4 Nomor 3 Desember, hal. 223-245Sutrisno. 2001. Analisis Faktor-faktor yang mempengaruhi Dividend Payout Ratio. TEMA, Volume II, Nomor 1, Maret 2001